2019
DOI: 10.2147/jpr.s189605
|View full text |Cite
|
Sign up to set email alerts
|

<p>An integrated safety analysis of combined acetaminophen and ibuprofen (Maxigesic<sup>&reg;</sup>/ Combogesic<sup>&reg;</sup>) in adults</p>

Abstract: IntroductionAcetaminophen (APAP) and ibuprofen (IBP) are two analgesic compounds with a long history of use. Both are considered safe at recommended over-the-counter daily doses. Chronic use, high doses, or concomitant medication can produce safety risks for both drugs. APAP is associated with increased risk of hepatic injury, while IBP can produce gastric bleeding and thromboembolic events. Using a combination of APAP and IBP provides superior analgesia without transgressing daily dose limits of each individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Meanwhile, of the 65 clinical trials on topical NSAIDs, 57% allowed patients to use acetaminophen as rescue therapy [ 120 ]. Furthermore, a supplementary data analysis summarizing four RCTs found that the concurrent use of oral acetaminophen and oral ibuprofen did not increase the risk of common adverse events [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, of the 65 clinical trials on topical NSAIDs, 57% allowed patients to use acetaminophen as rescue therapy [ 120 ]. Furthermore, a supplementary data analysis summarizing four RCTs found that the concurrent use of oral acetaminophen and oral ibuprofen did not increase the risk of common adverse events [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…When administered orally, paracetamol will suffer first-pass metabolism and be converted into p-aminophenol in the liver and then into N-(4-Hydroxyphenyl) arachidonylamide (AM404) in the brain. The AM404 is a potent agonist of the transient receptor potential vanilloid type 1 (TRPV1), a low-affinity ligand of the cannabinoid receptor type 1 (CB 1 ), an anandamide membrane transporter blocker, and a cyclooxygenase (COX) inhibitor [ 30 ]. When paracetamol is taken intravenously, it is spared from the first-pass process and the biosynthesis of AM404 is less extensive [ 31 ].…”
Section: Multimodal and Parenteral Analgesiamentioning
confidence: 99%
“…As previously reported, at this moment, the combination of ibuprofen with paracetamol is the unique parenteral analgesic FDC available on the market. Even when taken orally, this combination was shown to be an effective alternative to opioid-based analgesia [ 30 ]. However, there are a limited number of studies assessing the efficacy and safety of parenteral FDCs of ibuprofen/paracetamol [ 3 ].…”
Section: Parenteral Fixed-dose Combinationsmentioning
confidence: 99%
See 2 more Smart Citations